Evaluation of Students' Counseling Needs: A Quantitative Analysis - Ahmadi Dehrashid, Fatemeh; Salimi, Jamal; Isanejad, Omid (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The need for counseling and guidance is felt throughout life for all individuals, especially students. The aim of this study was to evaluate Iranian students’ counseling needs.Methods and Materials: This research is applied in terms of purpose, and the researcher's approach in organizing studies has been meta-analysis with an exploratory process. For collecting information appropriate to the research strategy, the systematic review method has been used. In this regard, through an internet search in scientific databases including Google Scholar, Jihad Daneshgahi website, ENSANI Portal, Noormags, and Civilica, efforts were made to collect published studies in the field under investigation. The results of this stage led to the identification and selection of 21 research works in the period from 2001 to 2021 that had the most thematic relevance to the present study. After screening the identified articles, 7 articles that had more similarities and consistency in terms of structure, content, and methodology compared to the other 14 articles were selected for analysis. The statistical sample of this study includes 2031 individuals, with the majority, 57.5%, being female and 42.5% male.Findings: According to the selected articles, students' counseling needs were categorized and examined in five areas: personal growth and development, occupational needs, educational needs, family and marriage needs, and emotional and psychological needs. The results confirmed the significant impact of all these five categories as essential counseling needs for students.Conclusion: It can be concluded that the needs and guidance required by students can be considered in several categories, and many of these needs can be addressed through empowerment and increasing students' resilience.